Parenting Strategy as an Effort to Prevent Underestimating Students - Mukid, M; Maksum, Muh. Nur Rochim; Shohib, Muhammad Wildan; Andhim, Muk (Universitas Muhammadiyah Surakarta, 2023)
This study aims to discover the mapping of the development and direction of Islamic Ecosystem research in publications indexed by Scopus. This study uses bibliometric analysis techniques to explore all publications indexed in the Scopus database on (Parenting Strategies as an Effort to Prevent Student Underestimation Attitudes Towards Teachers) from 2015 to 2023. The data was analyzed using Excel and R/R-Studio. VOSviewer is used to perform visual analysis of the occurrence of keywords and document citations simultaneously. The authors found 867 publications that fit the established functions, subjects, and criteria. Morals as a meaning in the aspect of emphasizing Islamic teachings are recommended for habituation since childhood. This is because childhood is more conducive to practicing good behavior habits. Educators need a mature plan for educating children in order to have an effective moral education strategy. The purpose of this study is to describe how the strategies of classroom teachers or subject teachers in optimizing students' morals in the learning process can run conductively. The results of this study show an annual growth rate of 1.13%, with the most publications on Parenting in 2023. The United States is the country with the most publications contributed by affiliation of The Ohio State University. Elpley N became the most prolific writer on the subject (12). The bibliometric analysis carried out is limited to Scopus data. Other national and international databases were not taken into account in this study. This study presents a brief overview of the literature accessible to researchers working in the field of Islamic Education and provides recommendations for future research.